Clinical characterisation and management outcomes of COVID-19 infection in pregnancy in a Nigerian tertiary hospital - Ijarotimi, Omotade A.; Ubom, Akaninyene E.; Awowole, Ibraheem O.; Ayegbusi, Ekundayo O.; Kuti, Oluwafemi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Literature on the antenatal and perinatal management and outcomes of COVID-19 infection in pregnancy in Nigeria and sub-Saharan Africa is gradually emerging but sparse. There is an urgent need to build up the knowledge base of COVID-19 infection in Nigerian pregnant women. The objective of the current study was to determine the clinical characteristics and management outcomes of COVID-19 infection in pregnancy at the Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC), Ile-Ife, Nigeria. Methods: A one-year retrospective review of all cases of COVID-19 infection in pregnancy managed at the OAUTHC. Relevant data were extracted from the case records of all cases managed using a purpose-designed proforma. Data collected was analysed using IBM-SPSS, version 24. Associations between categorical variables were assessed using chi square, with level of significance set at <0.05. Results: A total of 22 cases were managed. Majority (15, 68.2%) of the women were either asymptomatic or had mild symptoms. The commonest symptom was cough (8, 36.4%). The mean duration of admission was 6.6±4.2 days. The most common maternal and perinatal complication was preterm delivery/birth (3, 13.6%). There was no maternal mortality. The mean birth weight of the babies was 3226g±597g, with mean 1- and 5- minutes Apgar scores of 8.0±1.3 and 9.5±0.6 respectively. Conclusions: Although COVID-19 infection in pregnancy is an asymptomatic or mild infection in the majority of cases in Ile-Ife, Nigeria, it is associated with adverse maternal and perinatal outcomes. Further studies are recommended to determine transplacental transmission of COVID-19 infection and antibodies.